Pelatihan Penanaman Bibit Cabai dan Pembuatan Sabun Cuci Piring Ramah Lingkungan Sebagai Strategi Pemberdayaan Masyarakat Desa Timbang Lawan - Sarah Rizki Pebriani; Siti Salamah Br Ginting; Nur Hidayah Limbong; Nurika Kartika Dewi; Tri Hartanti (Lembaga Pengembangan Kinerja Dosen, 2024)
This community service in Timbang Lawan Village aims to empower residents through training in planting chili seeds and making environmentally friendly dish soap. Implementation methods include needs identification, theoretical and practical training, as well as post-training evaluation and monitoring. This training is designed to help people reduce household expenses, both through planting chilies for their own consumption and making dish soap independently. Apart from that, this program also opens up new business opportunities by selling chili harvests and homemade soap at local markets, which can increase income, especially for teenagers and housewives. The results of the activity show that the community has succeeded in reducing expenses while creating independent businesses that have the potential to support the local economy in a sustainable manner.